2020
DOI: 10.1186/s13244-019-0825-4
|View full text |Cite
|
Sign up to set email alerts
|

Gallstones top to toe: what the radiologist needs to know

Abstract: Gallstone-related disease can have significant associated morbidity and mortality worldwide. The incidence of gallstone-related disease in the Western world is on the increase. There are multiple different pathological manifestations of gallstone disease: the presentation, diagnosis and associated complications of which vary significantly depending on anatomical location. The role of imaging in gallstone-related disease is broad with radiology playing an essential role in the diagnosis, management and follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 16 publications
0
27
0
1
Order By: Relevance
“…Gallstones are solid rounded particles composed of a combination of cholesterol and bilirubin that form within the gallbladder and biliary system [2]. The primary risk factor for the development of gallstones is a high fat diet [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Gallstones are solid rounded particles composed of a combination of cholesterol and bilirubin that form within the gallbladder and biliary system [2]. The primary risk factor for the development of gallstones is a high fat diet [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that the results of performed tests were not related to the formation of gallstones. Despite the previous belief that there is a limited useful prediction for these tests for the formation of stones (Murphy et al, 2020). Kaldor et al reported that patients with cholecystitis who undergo laparoscopy for cholecystectomy have limited predictability of liver enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Three types of gallstones exist in practice: cholesterol, pigment, and mixed stones. Cholesterol stones account for 10% of all gallstones and result when cholesterol concentration exceeds the solubilizing capacity of bile which leads to the precipitation of cholesterol crystals [ 3 ]. They are pale yellow, formed only in the gallbladder and have a cholesterol content ranging from 50% to 100% [ 39 ].…”
Section: Reviewmentioning
confidence: 99%
“…Meanwhile, In Europe, ultrasound studies suggest a prevalence of 9%-21% [ 2 ]. The rising incidence of gallstone disease in western countries is considered to be a consequence of increasing obesity rates [ 3 ]. The age-long mnemonic of '5Fs' (fat, female, fertile, fair, and forty) has traditionally been used in medical school instructions to describe the risk factors for gallstone disease.…”
Section: Introductionmentioning
confidence: 99%